POLA PENDIDIKAN KARAKTER BERBASIS KELAS DI SMP ISLAM KHAIRA UMMAH PADANG - Efendi Efendi (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2016)
Abstract This study aims to determine the pattern of class-based character education through instructional and non-instructional approach to learning the Islamic Religious Education (PAI) in SMP Islam Khaira Ummah Ikur Koto Padang. The study also aims to determine the factors supporting and hindering the implementation of character education at the school. Qualitative methods have been used in carrying out this study. The data source is taken from six (6) informants, consisting of three (3) teachers PAI and three (3) class teachers. All data were taken using the in-depth interviews , and thematically analyzed using qualitative analysis tools. The results of this study clearly shows that there are five important themes implementation pattern of character education in the areas of instructional namely: (insert character values into the syllabus, lesson plans, learning materials, habituation to the students and make teachers as an example). As in the realm of non-instructional found three themes, namely: (insert character value to management, trust and consensus grade). In the supporting factors were found four themes, namely: (a curriculum that has been integrated, competent teachers, completeness of facilities and infrastructure, as well as the establishment of good cooperation between the school and parents). Whereas the inhibiting factors isfound two important themes, namely: (a lack of training for teachers on how to implement a character education and schools are often faced with various problems morals of students, especially students with problems from other schools and move to SMP Khaira Ummah).Keywords: Character Education, instructional and non-instructional approach, SMP Islam Khaira Ummah